The immunoregulation effect of tumor microenvironment in pancreatic ductal adenocarcinoma - Zhang, Jingchang; Li, Renfeng; Huang, Shuai (Frontiers in Oncology, 2022)
Pancreatic cancer has the seventh highest death rate of all cancers. The absence of any serious symptoms, coupled with a lack of early prognostic and diagnostic markers, makes the disease untreatable in most cases. This leads to a delay in diagnosis and the disease progresses so there is no cure. Only about 20% of cases are diagnosed early. Surgical removal is the preferred treatment for cancer, but chemotherapy is standard for advanced cancer, although patients can eventually develop drug resistance and serious side effects. Chemoresistance is multifactorial as a result of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment. Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. In this review, we comprehensively analyzed various components and pathways of the pancreatic cancer-related tumor microenvironment, as well as the interaction between tumor cells and the microenvironment, including immunosuppression, tumor dormancy and escape. Finally, we discussed a variety of immune components-oriented immunotargeting drugs in the tumor microenvironment from a clinical perspective.